The Effect of Spraying Eggs with Acetic Acid for Different Periods on the Characteristics of Hatched Chicks - Mohammed, Jaza Ali; Aziz, Chro Rafeq; Abdulla, Shanaz Mustafa; Mohammed, Mohammed Sardar; Shaker, Ahmed Sami (American Journal of Botany and Bioengineering, 2026)
The poultry industry plays a crucial role in global food production, with chicken eggs being a significant source of protein. Recent research has explored the application of organic acids, particularly acetic acid, to improve egg incubation and chick quality. This study aimed to evaluate the effects of spraying eggs with acetic acid for different periods on hatching characteristics and chick quality. A total of 320 fertile chicken eggs were divided into four groups, with each group treated with acetic acid for varying durations: 5 seconds (T2), 10 seconds (T3), and 15 seconds (T4). A control group (T1) was not treated. Eggs were incubated under standard conditions, and chick weight, egg volume, surface area, and shell index were measured post-hatching. The results showed that acetic acid treatment did not significantly affect egg weight, breadth, or length, but chick weight was significantly influenced by exposure duration, with T2 and T4 producing heavier chicks than T1 and T3. Egg volume and surface area were significantly affected by the treatments, with T4 showing the highest values. However, the shell index remained unchanged. The treatment had no significant effect on fertility, deformities, or sex ratio, but it significantly reduced mortality, indicating improved chick survival. These findings suggest that acetic acid application can enhance hatchability and chick quality, offering potential benefits for hatchery management without compromising egg shell integrity.